Utilizing Bloom's taxonomy to design a substance use disorders course for health professions students. Issue 3 (3rd July 2018) - Muzyk, Andrew J.; Tew, Chris; Thomas-Fannin, Allie; Dayal, Sanjai; Maeda, Reina; Schramm-Sapyta, Nicole; Andolsek, Kathryn; Holmer, Shelley
ABSTRACT: Background : Substance use disorders (SUDs) are a public health problem affecting millions of Americans. Despite their prevalence, there are few health care resources allocated for SUDs treatment. Relatively few health care professionals are exposed to SUDs education in their respective programs, which may be one reason for this resource insufficiency. In hopes of rectifying this gap, the authors developed a SUDs course for health professions students combining classroom learning with practical application to patient care. Methods : The authors used Bloom's taxonomy of cognitive, affective, and psychomotor learning domains as an educational framework to create numerous opportunities for students to deepen their knowledge, assess their attitudes, and develop their motivational interviewing skills. The primary outcome of the study was a comparison of students' scores on the Substance Abuse Attitude Scale (SAAS) pre- and post-course completion. Secondary outcome was to compare students' self-assessment scores of their patient counseling with residents' assessments of them on the Liverpool Communication Skills Assessment Scale (LCSAS). Results : One hundred twelve students participated in the authors' SUDs course over a 9-month period. Ninety-five students completed both the pre- and post-course SAAS surveys. The total SAAS survey score and individual domain scores for nonmoralizing, treatment optimism, and treatment intervention demonstrated significant improvement post-course. Eighty-nine students completed a motivational interview with a patient. Eighty students had a LCSAS self-assessment paired with a residents' assessment. Mean scores for individual items on the LCSAS for both groups' assessment were approximately 3.5, indicating that students' communication was assessed as "acceptable" to "good." Conclusions : This study demonstrates that Bloom's taxonomy was a useful educational framework to ensure a systematic development of the authors' SUDs course. Through participation in our course, students touched each of the 3 domains in Bloom's taxonomy. The authors believe their course design may serve as a framework for future SUDs courses.